Unhealthy leadership behavior and employee retention that shakes academic excellence in higher education from a critical realistic approach - Adeniyi Temitope Adetunji; Hieu Minh Vu (Revista on line de Política e Gestão Educacional)
Unhealthy leadership behavior also known as Toxic leader’s theory. It affects employee base and create environments to be less effective due to stress, devaluation, and potential job loss. And today, this challenge has also rocked academic excellence in higher education. This paper took a giant step to investigate unhealthy leadership behavior and employee retention that affects academic excellence and suggested a coping strategy by adopting a critical realist approach. This approach is used and adopted to understand the significant relationship between unhealthy leadership behavior, employee retention, and academic excellence. The study is centered on 48 head of units of universities both public and privately owned. The findings reveal that lack of job satisfaction and organizational commitment are rampant among higher educators due to unhealthy leadership behavior of which leads to implications on job satisfaction, job retention, and organizational commitment which are key components of organizational productivities.